Single-Cell RNA Sequencing of Brain Tissue Samples from Severe Traumatic Brain Injury Patients: A Protocol for Cellular Heterogeneity and Transcriptional Alteration Study - Albert, Venencia; Faruq, Mohammed; Verma, Satish; Sardana, Viren; Choudhary, Kumardeep; Agrawal, Deepak (Indian Journal of Neurotrauma, 2025)
Severe traumatic brain injury (sTBI) leads to significant morbidity and mortality, often complicated by cerebral edema and raised intracranial pressure (ICP). Understanding the molecular impact of these pathophysiological changes on the injured and adjacent noninjured brain is crucial for improving patient outcomes. Single-cell ribonucleic acid sequencing (scRNA-seq) offers a high-resolution approach to studying cellular heterogeneity and transcriptional alterations in TBI.This study aims to utilize scRNA-seq to analyze injured and noninjured brain tissue in patients with sTBI, identify differentially expressed genes, and characterize the cellular response to injury and its relation to ICP.A cross-sectional study will be conducted, and brain tissue samples will be collected from sTBI patients. Tissue samples will be obtained during decompressive craniectomy, processed, and analyzed using the 10× Chromium system. Libraries will be sequenced on Illumina NovaSeq 6000, and transcriptomic data will be analyzed using Seurat and other bioinformatics tools. Bulk RNA sequencing will be performed for validation.This study is expected to identify unique gene expression patterns associated with cerebral edema, characterize cellular responses in injured versus noninjured brain regions, and provide insights into molecular pathways contributing to secondary brain injury.By leveraging scRNA-seq, this study will provide a deeper understanding of the transcriptomic changes in sTBI. The findings may aid in discovering novel biomarkers and therapeutic targets, ultimately improving clinical management strategies for TBI patients.
Keywords: severe traumatic brain injury; single-cell RNA sequencing; cerebral edema; intracranial pressure; transcriptomics; biomarker discovery